WORK POSTURE, WORKING PERIOD & SMOKING HABITS CAUSE LOW BACK PAIN COMPLAINTS IN SHIPYARD WORKERS IN THE WELDING SECTION AT PT. X CITY BATAM IN 2023 - Leni Utami; Noviyanti; Tanosida K (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2024)
Musculoskeletal disorder (MSD) complaints that are often felt by almost all populations in the world are low back pain (LBP) complaints. Workers experience several risk factors: work posture, service length, and smoking habits. Squatting, standing, and sitting positions that are not ergonomic can cause the body to tire easily, causing musculoskeletal muscle disorders. This study aims to determine the relationship between work position, working period and smoking habit with low back pain complaints among shipyard workers in the welding section at PT X Batam City in 2023. This research is quantitative research with a cross-sectional study design. The population in this study were 110 welding shipyard workers (welder) with a sample size of 86 people (solving formula). The research instruments used were questionnaires and RULA worksheets. The sampling technique used was Simple Random Sampling. The statistical test used is a program on a computer where two kinds of data analysis will be carried out, namely univariate analysis and bivariate analysis. The statistical test results show a significant relationship between work posture and low back pain complaints, namely p-value = 0.000 and Pearson correlation = 0.871. There is a significant relationship between the working period with low back pain complaints, namely value = 0.000 and Pearson correlation = 0.490 & there is a significant relationship between smoking habits with low back pain complaints, namely value = 0.015 & pearson correlation = 0.261. There is a relationship between work posture, work period and smoking habits with low back pain complaints with a p-value <0.05. As for the suggestions in this study, for work postures, work station design can be carried out according to the welded products, while the working period for workers with high working periods can be limited to the number of working hours and to reduce smoking habits, the implementation of no smoking in the work environment area and appreciation for workers who do not smoke and proven good medical check-up results..